Analysis of Lean Manufacturing Strategies for Reducing Waste and Improving Production Efficiency in Medium and Large-Scale Industries - Deni Ahmad Taufik; Ade Suhara; Sukardi Sukardi; Isna Juwita (Metta : Jurnal Ilmu Multidisiplin, 2026)
The increasing complexity of global manufacturing competition requires industries to continuously improve operational efficiency while minimizing production waste. Medium and large-scale industries frequently encounter inefficiencies such as overproduction, waiting time, excess inventory, and product defects that negatively affect productivity and operational performance. This study aims to analyze lean manufacturing strategies for reducing waste and improving production efficiency in medium and large-scale industries through a qualitative literature review approach. Data were collected from relevant academic publications indexed in major scientific databases and analyzed using comparative thematic synthesis. The findings indicate that the most dominant lean manufacturing strategies include 5S, Kaizen, Just in Time (JIT), Value Stream Mapping (VSM), and Total Productive Maintenance (TPM), all of which contribute significantly to reducing non-value-added activities and improving production flow efficiency. The study also reveals that lean implementation differs according to organizational scale. Medium-sized industries tend to emphasize flexibility and participative improvement systems, whereas large-scale industries rely more heavily on integrated management structures and technological support. In addition, common implementation barriers include weak management commitment, employee resistance, and insufficient organizational readiness. This study contributes academically by developing a comparative synthesis of lean manufacturing implementation based on industrial scale, highlighting that the effectiveness of lean strategies is context-dependent rather than universally standardized. The findings emphasize the importance of adaptive and organization-sensitive lean implementation to achieve sustainable operational performance and industrial competitiveness.